Farm and Family Balance Baseline Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
This is the baseline dataset for the Farm and Family Balance Study. Sample consists of married sugarcane farmers associated with a large sugar company near Jinja, Uganda. All eligible farmers who agreed to participate are included. Both husbands and wives are interviewed. Survey includes questions regarding demographics, sugar production, other agricultural production, time use and employment, and empowerment.